2016
DOI: 10.1166/jnn.2016.10943
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Nanomechanical Properties of Single Trabecular Bone in Different Regions of Osteonecrosis of the Femoral Head

Abstract: This study aimed to compare the microstructure and nanomechanical properties of single trabecular bone in different regions of osteonecrosis of the femoral head. Osteonecrotic femoral heads were taken from 20 patients undergoing total hip arthroplasties between 2011 and 2014. Following incision, resin was embedded and polished, and divided into four regions according to the type of pathologic change; i.e., subchondral bone, and necrotic, sclerotic, and healthy regions. Indents from a single trabecular bone of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This observation is consistent with earlier studies, which suggest that vessel injury is an initiating factor for the pathological processes of osteonecrosis (19,25,47), and that osteonecrosis is a series of secondary pathological changes in response to ischemia (4). ER stress is known to activate three major signaling pathways, such as the PERK-ATF4 axis, ATF6 signal transduction, and IRE1a cascade (24,33,41). ER stress may act as a two-edged sword in such diseases as ONFH.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is consistent with earlier studies, which suggest that vessel injury is an initiating factor for the pathological processes of osteonecrosis (19,25,47), and that osteonecrosis is a series of secondary pathological changes in response to ischemia (4). ER stress is known to activate three major signaling pathways, such as the PERK-ATF4 axis, ATF6 signal transduction, and IRE1a cascade (24,33,41). ER stress may act as a two-edged sword in such diseases as ONFH.…”
Section: Discussionmentioning
confidence: 99%
“…All tests were conducted using the continuous stiffness measurement procedure as previously reported by Wang et al [20] . The Oliver-Pharr method, which assumes that any tip-sample contact is purely elastic, was used for data analysis [20,21] . Elastic modulus and hardness of trabecular were recorded.…”
Section: Nanoindentation Testmentioning
confidence: 99%
“…Bone reconstruction after osteonecrosis has an impact on the bone microstructures in the necrotic lesion, and alters the bone mechanical properties gradually 84 . Wang et al 85 . performed nanoindentation experiments on single bone trabeculae and found that the nanomechanical performance (elastic modulus and degree of hardness) of single trabecular bone in the necrotic region showed no difference with that in healthy bone region.…”
Section: Biomechanical Changes In Necrotic Femoral Headmentioning
confidence: 99%
“…Bone reconstruction after osteonecrosis has an impact on the bone microstructures in the necrotic lesion, and alters the bone mechanical properties gradually 84 . Wang et al 85 performed nanoindentation experiments on single bone trabeculae and found that the nanomechanical performance (elastic modulus and degree of hardness) of single trabecular bone in the necrotic region showed no difference with that in healthy bone region. The authors suggested that the direct result for the degradation of mechanical performance and subsequent femoral head collapse was the structure changes of bone trabeculae in macrostructure.…”
Section: Microstructural Changes In Necrotic Lesionmentioning
confidence: 99%